The provenance of obsidian artefacts from the Middle Kingdom harbour of Mersa/Wadi Gawasis, Egypt, and its implications for Red Sea trade routes in the 2nd millennium BC. (30th July 2020) - Lucarini, Giulio; Barca, Donatella; Manzo, Andrea
Abstract: This paper presents the results of the geochemical analysis carried out on the obsidian artefacts discovered at the archaeological site of Mersa/Wadi Gawasis, located along the Egyptian Red Sea coast, in between the modern cities of Safaja and Quseir. During the 12th and 13th Dynasties of Egypt the site hosted a port city from where the Egyptian expeditions set sail directed to the south, on both edges of the Red Sea. Six obsidian artefacts collected during the 1970s' research carried out at the site by A. Sayed, were geochemically analysed, together with five geological samples from the obsidian Kusrale source in Eritrea. The major element concentrations were determined by SEM-EDS analysis and the trace element concentrations were obtained by LA-ICP-MS method, a micro-destructive technique, capable of chemically characterizing the volcanic glass. A comparison of geochemical results obtained on the archaeological artefacts and geologic samples, together with the literature data on different geological obsidian outcrops from the Horn of Africa and the southwestern Arabian peninsula, allowed us to determine the provenance of the Mersa/Wadi Gawasis obsidian artefacts in both the Kusrale source of Eritrea, and the volcanic area of Dhamar Reda in Yemen. These results can provide further insights on ancient trade routes along the Red Sea during the early second millennium BC.